If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 1) + (x + 1) = 24 Reorder the terms: (1 + 3x) + (x + 1) = 24 Remove parenthesis around (1 + 3x) 1 + 3x + (x + 1) = 24 Reorder the terms: 1 + 3x + (1 + x) = 24 Remove parenthesis around (1 + x) 1 + 3x + 1 + x = 24 Reorder the terms: 1 + 1 + 3x + x = 24 Combine like terms: 1 + 1 = 2 2 + 3x + x = 24 Combine like terms: 3x + x = 4x 2 + 4x = 24 Solving 2 + 4x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 4x = 24 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 24 + -2 4x = 24 + -2 Combine like terms: 24 + -2 = 22 4x = 22 Divide each side by '4'. x = 5.5 Simplifying x = 5.5
| 29+6v=7(4v+1) | | 4.3+c=20.5 | | 57x-23-42x=-97 | | 3b+12=3(b-6)+4 | | 4x+3(x-5)=-12 | | (X-5)k=z | | 4(3a+5)+8(a+1)= | | k-(-3)=-3 | | 200+10(5)=100+30(5) | | 4x+2y+8=0 | | 3b-(b+1)=3(b-5) | | 6+.10x=5x+10 | | 4x-6+x+11=180 | | 3-5b+2b=-2-(1-b) | | x+(x+7)+3x=32 | | 5w+6w+15=3w+15 | | X+x+1+x+2=189 | | 2-4w=-10 | | X*x=9x | | X-3(2x+1)-12x=-2 | | 3x+4x-9=180 | | 1+(-6)+2x=x+4 | | 3000=-16t^2+5000 | | 6(x-6)=8(x-1) | | -2.7tsquared+96t=-16tsquared+96t | | 0=-2x^2+10 | | 3p^2+28p+32=0 | | 150+15h=25h | | 6(x-1)=8(x-1) | | r^2-11x+5=0 | | 16t+14t=270 | | -(-8x+4)-2x=-12 |